LncRNA MRAK159688 facilitates morphine tolerance by promoting REST-mediated inhibition of mu opioid receptor in rats. (15th March 2022) - Deng, Meiling; Zhang, Zengli; Xing, Manyu; Liang, Xia; Li, Zhengyiqi; Wu, Jing; Jiang, Shasha; Weng, Yingqi; Guo, Qulian; Zou, Wangyuan
Abstract: Morphine tolerance (MT) caused by the long-term use of morphine is a major medical problem. The molecular mechanism of morphine tolerance remains elusive. Here, we established a morphine tolerance model in rats and verified whether the long noncoding RNA (lncRNA) MRAK159688 is involved in morphine tolerance and its specific molecular mechanism. We show the significant upregulation of MRAK159688 expression in the spinal cord of morphine-tolerant rats. Overexpression of MRAK159688 by a lentivirus reduces the analgesic efficacy of morphine and induces pain behavior. Downregulation of MRAK159688 using a small interfering RNA (siRNA) attenuates the formation of morphine tolerance, partially reverses the development of morphine tolerance and alleviates morphine-induced hyperalgesia. MRAK159688 is located in the nucleus and cytoplasm of neurons, and it colocalizes with repressor element-1 silencing transcription factor (REST) in the nucleus. MRAK159688 potentiates the expression and function of REST, thereby inhibiting the expression of mu opioid receptor (MOR) and subsequently inducing morphine tolerance. Moreover, REST overexpression blocks the effects of MRAK159688 siRNA on relieving morphine tolerance. In general, chronic morphine administration-mediated upregulation of MRAK159688 in the spinal cord contributes to morphine tolerance and hyperalgesia by promoting REST-mediated inhibition of MOR. MRAK159688 downregulation may represent a novel RNA-based therapy for morphine tolerance. Highlights: MRAK159688 is up-regulated during induction of morphine tolerance. MRAK159688 contributes to morphine tolerance and morphine-induced hyperalgesia. MRAK159688 downregulation intervenes morphine tolerance. MRAK159688 may promote REST-mediated MOR inhibition to induce morphine tolerance.